Project management techniques and marketability of certain low-cost housing projects a correlation study - Guillermo, Fe Marian Grail E. (College of Architecture, University of the Philippines Diliman, 2003)
This study was undertaken primarily to test the hypothesis that project management techniques significantly increases marketability of housing. This research was also used to identify and clarify the role of project management techniques in marketability of housing. How is project management techniques related to the marketability of housing How is marketability of housing affected by project management techniques This thesis identified the relationship of project techniques in the marketability of five low-cost housing projects in two phases, first phase or first study surveyed the years 1997-2000, and second phase or second study surveyed the years 2001 to 2003. Correlation ratios between PMT and marketability of housing they produced were then established from these data. This research also assessed the marketability ratings of certain low-cost housing projects of five low-cost housing developers, first between the years 1997-2000, then in the years 2001 to 2003. This study used interview and survey as a method of collecting data from this research's respondents, notably the project engineers and marketing managers of the five low-cost housing developers being surveyed. This method was used twice for the two studies done by this researcher for this thesis. Data from the first study noted that project management techniques used in low-cost housing development is significantly correlated with the marketability of the low-cost housing projects they produce. The first study concluded that project management techniques affect marketability of low-cost housing projects though minimally and even inversely. The study concluded that there are problems besetting both the use of project management techniques and the marketability of low-cost housing they produce. Data from the second study noted further the relationship between PMT and marketability of low-cost housing. The study showed that PMT still affects marketability, though not significantly but otherwise directly or positively. The second study further established that there are other factors which greatly affect the marketability aspect of housing other than PMT. The marketability of low-cost housing in the second study increased even when the same PMTs were used by the same developers. From the determined relationship between project management techniques and the marketability aspect of housing, recommendations were then formulated for the improvement of the marketability of low-cost housing projects.